Transformational Leadership as a Driver of Employee Engagement in CSR Programs - Rojak, Jeje Abdul (Journal of Social Science Studies, 2025)
This research examines the relationship between transformational leadership and employee engagement in corporate social responsibility programs through a qualitative literature study. By synthesizing findings from various published studies, this review identifies multiple pathways through which transformational leadership influences employee participation in CSR activities. The analysis reveals that employees perceive transformational leadership as affecting CSR engagement through inspiration, intellectual stimulation, individualized consideration, role modeling, and supportive psychological climate. Organizational identification, empowerment, effective communication, recognition, capacity building, and meaning creation emerge as key mechanisms linking transformational leadership to CSR participation. The influence proves cumulative and generates positive dynamics in which individual participation reinforces collective engagement. These findings enrich theoretical understanding of leadership and CSR relationships while offering practical guidance for organizations seeking to enhance employee participation in social responsibility initiatives.